Pengaruh Prestasi Kerja, Kompetensi dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT Nasco (Indopine) di Kabupaten Deli Serdang - Br Sitepu, Elia Meininta; Wulandari, Niken; Rahayu, Sri (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the influence of work performance, competence, and organizational culture on employee performance at PT Nasco (Indopine) in Deli Serdang Regency. The background of this study is based on the problem of suboptimal employee performance, particularly in the aspects of initiative and punctuality, as well as low work performance, competence, and implementation of organizational culture. This research employed a quantitative methodology using a census strategy including 68 permanent and contract employees. Data were gathered via surveys and processed employing multiple linear regression using SPSS version 26. The findings indicated that, both individually and collectively, the variables of job performance, competence, and organizational culture exerted a favorable and significant influence on employee performance. These findings indicate that improved employee performance can be achieved through increased work target achievement, strengthening skills and experience, and implementing a positive organizational culture. Therefore, a comprehensive human resource management approach is crucial for increasing productivity and work effectiveness in a company environment.